Contralateral breast cancers: Independent cancers or metastases?. Issue 2 (28th September 2017) - Begg, Colin B.; Ostrovnaya, Irina; Geyer, Felipe C.; Papanastasiou, Anastasios D.; Ng, Charlotte K.Y.; Sakr, Rita A.; Bernstein, Jonine L.; Burke, Kathleen A.; King, Tari A.; Piscuoglio, Salvatore; Mauguen, Audrey; Orlow, Irene; et al.
Abstract : A cancer in the contralateral breast in a woman with a previous or synchronous breast cancer is typically considered to be an independent primary tumor. Emerging evidence suggests that in a small subset of these cases the second tumor represents a metastasis. We sought to investigate the issue using massively parallel sequencing targeting 254 genes recurrently mutated in breast cancer. We examined the tumor archives at Memorial Sloan Kettering Cancer Center for the period 1995–2006 to identify cases of contralateral breast cancer where surgery for both tumors was performed at the Center. We report results from 49 patients successfully analyzed by a targeted massively parallel sequencing assay. Somatic mutations and copy number alterations were defined by state‐of‐the‐art algorithms. Clonal relatedness was evaluated by statistical tests specifically designed for this purpose. We found evidence that the tumors in contralateral breasts were clonally related in three cases (6%) on the basis of matching mutations at codons where somatic mutations are rare. Clinical data and the presence of similar patterns of gene copy number alterations were consistent with metastasis for all three cases. In three additional cases, there was a solitary matching mutation at a common PIK3CA locus. The results suggest that a subset of contralateral breast cancers represent metastases rather than independent primary tumors. Massively parallel sequencing analysis can provide important evidence to clarify the diagnosis. However, given the inter‐tumor mutational heterogeneity in breast cancer, sufficiently large gene panels need to be employed to define clonality convincingly in all cases. Abstract : What's new? In cases of breast cancer, if a tumor appears in the second breast, it's usually a new, unrelated cancer – but sometimes, as this paper shows, it's a metastasis of the original tumor. These authors wondered just how often contralateral breast cancer arises due to metastasis, so they embarked on a huge sequencing effort to compare 49 tumors pairs at 254 different genes. In six cases, genetic similarities suggested that the tumors most likely had a shared heritage. This new way of understanding CBC could alter the way the disease is managed clinically.